Early and mid-embryonic upregulation of chloride, calcium, and sodium transporter genes mark functional maturation of the chorioallantoic membrane in broiler embryos - Amaz, Sadid Al; Poudel, Suman; Jha, Rajesh; Mishra, Birendra (Frontiers in Physiology, 2025)
The chorioallantoic membrane (CAM) is essential for ion transport, acid-base homeostasis, and respiratory gas exchange during chicken embryonic development. The temporal expression of ion transporter-related genes in CAM is still inadequately investigated. This study examined the developmental regulation of genes associated with the transport of calcium (Ca), sodium (Na), bicarbonate (HCO3−), potassium (K), protons (H+), and chloride (Cl−) in the CAM at embryonic days (ED) 12, 15, and 18. Six hundred fertilized Cobb 500 broiler eggs were obtained from a local hatchery. After candling, on ED 10, a total of 236 eggs were selected for this experiment. All the eggs were incubated in an automated temperature regulation of 37.5°C, 55% relative humidity (RH), and egg rotation every 2 h. On days 12, 15, and 18 of the embryonic period, CAM tissues were collected (n = 6 per group), total RNA isolated, and target genes were analyzed using qPCR. At ED 12, chloride transporter genes (CLCN2, SLC4A1, and SLC26A9) were significantly upregulated compared to ED 18 (P < 0.05). At ED 15, calcium transporters (ATP2A2, ATP2A3, ITPR1, ATP2B4, SLC8A1, SLC8A3, TRPV6, and RYR1) were significantly upregulated compared to ED 12 and/or ED 18 (P < 0.05). Sodium transporters (ATP1A1 and SCNN1B), bicarbonate transporters (SLC4A4 and SLC4A10), potassium transporters (KCNMA1), and proton transporters (CA7 and CA9) were also significantly upregulated at ED 15 compared to ED 12 (P < 0.05). At ED 18, sodium transporter (ATP1B1, SCNN1A, and SGK1) and proton transporter (CA2) were significantly upregulated compared to ED 12 and/or ED 15 (P < 0.05). The results indicate a synchronized, stage-dependent transcriptional activation of ion transporter genes in the CAM, especially at the mid-embryonic stage.